2015
DOI: 10.4049/jimmunol.1402909
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Directly Suppresses Th1 Cell Differentiation and Alleviates Experimental Autoimmune Encephalomyelitis

Abstract: Human C-reactive protein (CRP) is a serum soluble pattern recognition receptor (PRR) that serves as a marker of inflammation and directly contributes to innate immunity. Herein we show that human CRP also directly contributes to adaptive immunity, i.e. native CRP binds specifically to human Jurkat T cells and to mouse naïve CD4+ T cells and modulates their T helper (Th) 1 and Th2 responses. In vitro both exogenously added (purified) and endogenously expressed (via transfection) human CRP inhibited Th1 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 57 publications
5
30
2
Order By: Relevance
“…Our studies suggest that specific isoforms of CRP mediate chronic inflammation, in part, by modulating the polarization of monocytes and T lymphocytes migrating across the endothelial layer. Recently, it has been reported that CRP (untested for isoform content) directly stimulated Th2 polarization of the human Jurkat T cell line [38], and here we report that pCRP promoted a Th2 response with M2 macrophage differentiation, whereas mCRP promoted a Th1 response with M1 macrophage differentiation. By logical extension, the effect of CRP isoforms on T lymphocytes in the progression of atherosclerotic plaques presents a promising potential area of study.…”
Section: Discussionsupporting
confidence: 61%
“…Our studies suggest that specific isoforms of CRP mediate chronic inflammation, in part, by modulating the polarization of monocytes and T lymphocytes migrating across the endothelial layer. Recently, it has been reported that CRP (untested for isoform content) directly stimulated Th2 polarization of the human Jurkat T cell line [38], and here we report that pCRP promoted a Th2 response with M2 macrophage differentiation, whereas mCRP promoted a Th1 response with M1 macrophage differentiation. By logical extension, the effect of CRP isoforms on T lymphocytes in the progression of atherosclerotic plaques presents a promising potential area of study.…”
Section: Discussionsupporting
confidence: 61%
“…What is surprising is that CRP could shift the monocyte response to an M2 phenotype without affecting that T cell response. M2 macrophages have been observed to direct T cell activation and maturation , and so we expected a change from a Th1 to a Th2 response in cultures with CRP, especially since CRP has been reported to suppress Th1 cell differentiation . Others have shown that oxidized lipids induce maturation of naïve T cells to Th1 cells ; thus it is possible that the Th1 response could become chronic or predominant based on continuous recruitment of new cells to a proinflammatory phenotype (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of crystal structure, a specific inhibitor blocking the binding of pentameric CRP to phosphorylcholine has been developed showing beneficial effects in a rat model undergoing acute myocardial infarction (49). However, given the putative function of CRP in host defense (50) and its (tonic and global) anti-inflammatory activities (4,51), the systemic long-term inhibition appears to be problematic. mCRP may be the functionally dominant conformation of CRP active in inflammatory loci (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%